2013
DOI: 10.1371/journal.pone.0070583
|View full text |Cite
|
Sign up to set email alerts
|

Phytoliths in Pottery Reveal the Use of Spice in European Prehistoric Cuisine

Abstract: Here we present evidence of phytoliths preserved in carbonised food deposits on prehistoric pottery from the western Baltic dating from 6,100 cal BP to 5750 cal BP. Based on comparisons to over 120 European and Asian species, our observations are consistent with phytolith morphologies observed in modern garlic mustard seed (Alliaria petiolata (M. Bieb) Cavara & Grande). As this seed has a strong flavour, little nutritional value, and the phytoliths are found in pots along with terrestrial and marine animal res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 31 publications
0
28
0
Order By: Relevance
“…It is possible that low amounts of plant-derived lipids may have been masked by lipidrich animal products. To investigate further, plant starch granules and phytoliths (silica bodies) were extracted from interior and exterior charred deposits from 15 Incipient and 6 Early Jōmon vessels using established protocols optimized for pottery residues (33,34). In each case the number of starch granules (<1 count per mg −1 ) and phytoliths (<10 count per mg −1 ) were very low and significantly indistinguishable from exterior surface deposits [Kruskal-Wallis, χ 2 (phytoliths) = 0.0385, P = 0.8444; χ 2 (starch) = 1.6662, P = 0.1968] (Table S4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that low amounts of plant-derived lipids may have been masked by lipidrich animal products. To investigate further, plant starch granules and phytoliths (silica bodies) were extracted from interior and exterior charred deposits from 15 Incipient and 6 Early Jōmon vessels using established protocols optimized for pottery residues (33,34). In each case the number of starch granules (<1 count per mg −1 ) and phytoliths (<10 count per mg −1 ) were very low and significantly indistinguishable from exterior surface deposits [Kruskal-Wallis, χ 2 (phytoliths) = 0.0385, P = 0.8444; χ 2 (starch) = 1.6662, P = 0.1968] (Table S4).…”
Section: Resultsmentioning
confidence: 99%
“…Although starch granules deteriorate during cooking, low counts of more thermally durable phytoliths were recorded in the same samples, supporting the proposition that an absence of plant remains was not a result of poor preservation. Although plant processing remains a possibility, as lack of evidence is always difficult to interpret, we argue that given: (i) the optimal organic conditions for preservation at Torihama, (ii) the fact that plant microfossils have been readily extracted from other examples of hunter-gatherer pottery (33,34), (iii) the elevated bulk δ 15 N values, (iv) the low atomic C:N ratios, and (v) the overwhelming molecular evidence for lipids derived from aquatic animals, the absence of significant plant processing in pottery from Torihama can be reasonably concluded. (Table S2) …”
Section: Resultsmentioning
confidence: 99%
“…Although organic molecules are prone to degradation processes during pottery use or during the post-depositional period, it has been found that adequate concentrations of lipids can be preserved either as absorbed residues or visible food crusts and retrieved through organic solvent extraction (Heron, Evershed 1993;Evershed 2008;Craig 2004;Saul et al 2013).…”
mentioning
confidence: 99%
“…While isotopic studies seem to be the current trend in archaeological studies of agriculture and subsistence, traditional paleobotanical analyses of pollen and phytoliths continue to yield exciting results. For instance, Hayley Saul and colleagues () have just found the earliest direct evidence of spices (phytoliths of mustard garlic) being used to flavor European cuisine in the western Baltic region, introduced at the same time that domesticates first appear in this area.…”
Section: Economy and Productionmentioning
confidence: 99%